Розробка технологи поверхнево-активних речовин Rhodococcus erythropolis EK-1 з використанням промислових відходів - Софілканич (Морозова), Анна Павлівна (My University, 2013)
Розроолена технолопя дає змогу отримати до 10 г/дм ПАР за умов культивування R. erythropolis ЕК-1 на пересмаженій олії (2 %), використання інокуляту, вирощеного на мелясі, внесения у середовище 0,1 % глюкози на початку культивування та 0,1 мМ Си у експоненцшнш фазі росту. Показано, що за дії препаратів ПАР штаму ЕК-1 виживання мікроорганізмів, у тому числі й фітопатогенних бактерій, становило 10-70 % порівняно із зразками без ПАР. За обробки препаратами ПАР стоматологічних матеріалів спостерігали зниження адгезії клітин бактерій та дріжджів на 45-65 % порівняно із необробленими поверхнями.

The strain of oil oxidizing bacteria, identified as R. erythropolis EK-1, was isolated from oil-contaminated water and soil samples at the Department of Biotechnology and Microbiology of National University of Food Technologies in previous studies. The ability of strain EK-1 to synthesize surfactants on w-hexadecane and ethanol was established and the composition of nutrient medium and conditions of producer’s cultivation were optimized. The physiological fundamentals of surfactant synthesis regulation were defined during the growth of R. erythropolis EK-1 on hydrophilic and hydrophobic compounds and technology was scaled to fermentation equipment The possibility of replacing of high-cost substrates («-hexadecane and ethanol) for the surfactant biosynthesis by R. erythropolis EK-1 with industrial waste (oil and fat industry, fried sunflower oil, glycerol, liquid paraffin) was established. The highest rates of surfactants synthesis were observed on oil containing substrates and exceeded those on w-hexadecane and ethanol by 1,3-3 folds.
Keywords: пересмажена соняшникова олія; інтенсифікація біосинтезу; поверхнево-активні речовини; Rhodococcus erythropolis ЕК-1; fried; surface-active substances; кафедра біотехнології і мікробіології